The Relationship between Linguistic Intelligence and Computational Thinking among Fifth Grade Students of Elementary School - Atmojo, Idam Ragil Widianto; Ardiansyah, Roy; Widianto, Joko Tri; Saputri, Dwi Yuniasih; Faizah, Maryam (Mimbar Sekolah Dasar, 2024)
This study aims to determine whether there is a relationship between linguistic intelligence and computational thinking. The research method employed is quantitative, utilizing a correlational research design. The research sample comprised 73 students from 4 elementary schools in the Laweyan District, Surakarta City. Data collection involved a test instrument in the form of a descriptive test to assess both linguistic intelligence and computational thinking. Data analysis included prerequisite tests and hypothesis testing. The results indicate a significant overall relationship between linguistic intelligence and computational thinking, with a significance value of 0.000 (p 0.05) and a Pearson correlation coefficient of 0.493 with the moderate category. The relationship between each indicator of linguistic intelligence and computational thinking shows significant and positive correlations for the rhetoric, explanation, and metalinguistics indicators, with p 0.05. In contrast, the mnemonics indicator does not demonstrate a significant relationship, with a p 0.05.  These findings can serve as a reference for further research. The significant relationship between linguistic intelligence and computational thinking suggests that enhancing linguistic skills, particularly rhetoric, explanation, and metalinguistics, could improve students' computational abilities, guiding future educational strategies.